PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN ISLAMIC BRANDING TERHADAP KEPUTUSAN PEMBELIAN DI HYPERMART - Haryo Bimo (2020)
With the presence of modern retail, it is hoped that the marketed products can provide information on the benefits of the products offered in a precise and targeted manner. In addition to making it easier for consumers to buy all kinds of products they need in a way that is more convenient under one roof and easy in their transactions. This research is a quantitative study of existing products at the Hypermart retail. The purpose of this study is to find out whether product purchasing decisions at Hypermart retail are influenced by product quality, service quality and Islamic Branding. using probability sampling techniques and random sampling methods. Data collection is done by distributing questionnaires online to respondents. The technical analysis used is the PLS (Partial Least Square) analysis method using SmartPLS 3.0. The results of this study indicate that product quality and Islamic Branding variables significantly influence purchasing decisions. While the service quality variable has no influence and is significant on purchasing decisions.